HEART DISEASES IN THE ELDERLY (Homoeopathy for All, 2023)
Recent decades have witnessed striking growth in the number of older adults throughout the world, largely due to improved public health, nutrition, and medical care. Ironic all y, aging also catalyzes fundamental changes that increase susceptibility to Cardiovascular disease (CVD) such that CVD is endemic in the burgeoning senior population.Aging is a continuum of changes that mount over time, with pace and nature of progression varying depending on each person's circumstances.
Keywords: striking; nutrition; circumstance